2022
DOI: 10.1097/mpg.0000000000003580
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping of Eosinophilic Esophagitis Based on Disease Presentation in a pediatric Cohort

Abstract: Objective: Eosinophilic esophagitis (EoE) is an immune-mediated inflammatory disease characterized by eosinophilic infiltration of esophageal tissue. Subtyping of EoE patients could be useful in predicting therapeutic response. We propose clinical subtypes, apply them to our pediatric EoE population retrospectively, and assess therapy choices and remission at one year. Methods: A retrospective chart review of pediatric patients diagnosed with EoE was conducted. Patients were grouped into proposed subtypes (sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Indeed, some previous data have suggested that once a certain threshold of Th2‐mediated inflammation is surpassed, there may be a drop in PPI responsiveness 14 . Another consideration is that an allergic phenotype in EoE may indicate more severe disease, and prior pediatric studies have suggested that those with PPI‐r‐EoE tend to have mild to moderate disease 24,25 . Finally, reflux and refluxate‐induced mucosal injury may play a less prominent role in EoE patients with allergic phenotype, further reducing the impact of PPI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some previous data have suggested that once a certain threshold of Th2‐mediated inflammation is surpassed, there may be a drop in PPI responsiveness 14 . Another consideration is that an allergic phenotype in EoE may indicate more severe disease, and prior pediatric studies have suggested that those with PPI‐r‐EoE tend to have mild to moderate disease 24,25 . Finally, reflux and refluxate‐induced mucosal injury may play a less prominent role in EoE patients with allergic phenotype, further reducing the impact of PPI therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 Ascertaining the true demographics of EGIDs also helps us understand the heterogeneity of these diseases through identification of various disease phenotypes. As phenotypes are recognized, we can explore genotypic and possible mechanistic differences 17 , 44 and tailor therapies for better outcomes. On a larger scale, understanding disease demographics is crucial for resource allocation for clinical care, research, community engagement, and population health.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are warranted to further test the reproducibility and generalizability of the web‐based predictive models in different populations to make it more robust and reliable, as well as to update the existing web‐based predictive models to provide predictive probability for severity of LPF by sub‐scores (0–3) per EoEHSS. It is conceivable that we might be able to create models to prospectively predict LPF in different EoE phenotypes (17) and consistent evaluation of LPF (18) in EoE patients with high degree of confidence.…”
Section: Discussionmentioning
confidence: 99%